The Impact of Differences between Millennial Generation and Generation Z on Communication Patterns at Madrasa Ali Imron - Nasution, Maimunah Boru; Rasyid, Abdul (UNIVERSITAS PAKUAN, 2023)
This study seeks to determine the effect of generational differences between millennials and generation Z on Madrasa Ali Imron's communication patterns. The research procedure employed is qualitative and descriptive in nature. On the basis of observations and interviews, it has been determined that there are disparities in the communication styles of the two generations due to the increasing sophistication of technology. Thus, communication patterns with multiple directions entice students to interact in cyberspace until they become addicted and directly affect student interactions. The influence of differences in communication patterns is the occurrence of discommunication, which results in students not comprehending the message conveyed, and the occurrence of discommunication, such as misunderstandings when receiving messages.